2019
DOI: 10.1177/2150135119843887
|View full text |Cite
|
Sign up to set email alerts
|

Right Ventricular Dominance Is Associated With Inferior Outcomes After the Extracardiac Fontan

Abstract: Background: Investigations of ventricular dominance and outcomes after the Fontan procedure have shown conflicting results. This may be due to the inclusion of multiple modifications of the Fontan or the omission of recently identified complications of the procedure. We examined the association between right ventricular dominance (RVD) and morbidity/mortality in a contemporary cohort following the extracardiac (EC) Fontan. Methods: We studied all pediatric patients at our center who underwent a predominantly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…7 A reason could be due to an earlier progression to FO in single ventricle lesions with right dominance (such as HLHS) to better preserve ventricular function as there is conflicting information suggesting poor long-term FO outcomes with right sided dominant lesions such as HLHS. 18 Interestingly, the patients in the Western region of the United States were more likely to have an LF (27% vs. 12%, p = −.003). It is difficult to ascertain the reason behind this observation.…”
Section: Discussionmentioning
confidence: 95%
“…7 A reason could be due to an earlier progression to FO in single ventricle lesions with right dominance (such as HLHS) to better preserve ventricular function as there is conflicting information suggesting poor long-term FO outcomes with right sided dominant lesions such as HLHS. 18 Interestingly, the patients in the Western region of the United States were more likely to have an LF (27% vs. 12%, p = −.003). It is difficult to ascertain the reason behind this observation.…”
Section: Discussionmentioning
confidence: 95%
“…Several authors have previously reported worse outcomes for patients with an anatomical FSRV during the Fontan pathway 8, [27][28][29] . A FSRV resulted to have a lower EF and reduced myocardial functional reserve when compared to FSLV, possibly related to an unsatisfactory functional adaptation to pressure and volume overload 11 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Systemic right ventricular morphology appears to be associated with an adverse outcome, reduced exercise capacity, and reduced ventricular function after the Fontan operation. 2 The synchronization of electrical conduction and mechanical activity of the heart is the premise of normal systolic function, and worsening RV mechanical dyssynchrony may be associated with an overall decline in RV function. 3 Therefore, quantitative assessment of ventricular function and dyssynchrony is important for predicting the outcome of the Fontan operation in children with an FSRV.…”
Section: Introductionmentioning
confidence: 99%